A self-monitoring precision calibration light source for the IceCube Upgrade. (29th September 2021) - Henningsen, F.; Boehmer, M.; Eller, P.; Fruck, C.; Gärtner, A.; Geilen, L.; Gernhäuser, R.; Heggen, H.; Holzapfel, K.; Khera, N.; Papp, L.; Pertl, T.; et al.
Abstract: With neutrino astronomy on the rise, calibration aspects of large-volume detectors are becoming one of the key targets to boost detector performance. In the scope of the IceCube Upgrade planned for the South Pole season of 2022/23, we developed a novel, isotropic, self-monitoring, precision calibration light source. We present the device characteristics as well as first studies of calibration impacts for different detection environments.